Disease-free survival as a measure of overall survival in resected pancreatic endocrine neoplasms. Issue 5 (May 2020) - Ricci, Claudio; Partelli, Stefano; Ingaldi, Carlo; Andreasi, Valentina; Campana, Davide; Muffatti, Francesca; Alberici, Laura; Giorgi, Cecilia; Casadei, Riccardo; Falconi, Massimo
Abstract : Overall survival (OS) is considered as the standard measure of outcome in oncology. However, considering that resectable pancreatic neuroendocrine neoplasms (Pan-NENs) usually have a long OS, the feasibility of prospective studies is questionable due to a long follow-up period needed. The primary endpoint was to validate the use of disease-free survival (DFS) as a surrogate measure of OS. The secondary endpoint was to calculate the gain in sample size using DFS instead of OS in hypothetical prospective studies with two parallel groups. A systematic review of studies reporting both OS and DFS in resected Pan-NENs was carried out. Multivariate linear regression analysis was used to evaluate if DFS predicts the OS in patients undergoing radical resection. Monte Carlo simulation was performed to estimate the gain in sample size, supposing the use of DFS instead of OS, to evaluate a hypothetical adjuvant treatment after surgery in a randomized trial. Six studies reporting data about seven cohorts of resected Pan-NENs were included, for a total of 1088 patients. The median OS and DFS were 144 (27–134) and 122 (50–267) months, respectively. There was a significant correlation between DFS and OS ( R 2  = 0.988; P  = 0.035). Monte Carlo simulations showed that the number of patients needed to demonstrate a significant reduction of probability of a 'target event' in a hypothetical two-arm group exploring the hypothetical role of adjuvant therapy was reduced using DFS instead OS. This finding supports the legitimacy of using DFS as an acceptable surrogate for OS in surgical clinical trials.